Helminth infection and helminth-derived products: A novel therapeutic option for non-alcoholic fatty liver disease - Liu, Xi; Jiang, Yuyun; Ye, Jixian; Wang, Xuefeng (Frontiers in Immunology, 2022)
Non-alcoholic fatty liver disease (NAFLD) is closely related to obesity, diabetes, and metabolic syndrome (MetS), and it has become the most common chronic liver disease. Helminths have co-evolved with humans, inducing multiple immunomodulatory mechanisms to modulate the host’s immune system. By using their immunomodulatory ability, helminths and their products exhibit protection against various autoimmune and inflammatory diseases, including obesity, diabetes, and MetS, which are closely associated with NAFLD. Here, we review the pathogenesis of NAFLD from abnormal glycolipid metabolism, inflammation, and gut dysbiosis. Correspondingly, helminths and their products can treat or relieve these NAFLD-related diseases, including obesity, diabetes, and MetS, by promoting glycolipid metabolism homeostasis, regulating inflammation, and restoring the balance of gut microbiota. Considering that a large number of clinical trials have been carried out on helminths and their products for the treatment of inflammatory diseases with promising results, the treatment of NAFLD and obesity-related diseases by helminths is also a novel direction and strategy.